1999
DOI: 10.1007/s004210050598
|View full text |Cite
|
Sign up to set email alerts
|

Water and electrolyte shifts with partial fluid replacement during exercise

Abstract: In this study, we examined whether athletes, who typically replace only approximately 50% of their fluid losses during moderate-duration endurance exercise, should attempt to replace their Na+ losses to maintain extracellular fluid volume. Six male cyclists performed three 90-min rides at 65% of peak O2 uptake in a 32 degrees C environment and ingested either no fluid (NF), 1.21 of water (W), or saline (S) containing 100 mmol of NaCl x l(-1) to replace their electrolyte losses. Both W and S conditions decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 31 publications
0
28
0
3
Order By: Relevance
“…Our group has much experience with ISEs, from developing new ionophores to their application including environmental, industrial and physiological measurements 18,[32][33][34][35][36] . One of the most successful of these ionophores is a calix [4]arene based sodium ionophore (Sigma), which we use in the SSB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has much experience with ISEs, from developing new ionophores to their application including environmental, industrial and physiological measurements 18,[32][33][34][35][36] . One of the most successful of these ionophores is a calix [4]arene based sodium ionophore (Sigma), which we use in the SSB.…”
Section: Resultsmentioning
confidence: 99%
“…Dehydration for example can manifest itself as an increased sodium concentrations in sweat during exercise, so the possibility of monitoring this quantitatively in real-time is an appealing prospect 1 . Currently, for studies involving athletic performance, instead of directly analysing specific electrolyte concentrations, available fluid volumes are usually inferred only from body weight loss and urine output volumes over a set period of exercise, with electrolyte concentrations only measured separately and retrospectively [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies at ultra-endurance races such as an Ironman triathlon showed that oral sodium supplementation was not necessary to prevent hyponatremia (Hew-Butler et al 2006;Speedy et al 2002). Also sodium ingestion may not be of much advantage when athletes replace only *50% of their fluid loss during performances at 32°C (Sanders et al 1999). Sodium supplementation might, however, be of importance in a hot environment.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, variations in urine specific gravity and osmolality lag behind rapid changes in sweat losses or fluid intake (42). Besides having a potential influence on urine hydration status measures, CHO-E also may have enhanced (compared with water) total body hydration by ensuring greater fluid retention and distribution to all fluid compartments (30,31,50,51) and may have contributed to minimizing T C and cardiovascular strain during bout 2 (9).…”
Section: Repeated-bout Exercise In the Heat In Young Athletesmentioning
confidence: 99%